PENGARUH BERBAGAI MEDIA TANAM DAN DOSIS PUPUK ANORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI EDAMAME (Glycine max (L.) Merr.) DI POLYBAG - Nurul Fadlilah; Rahmad Jumadi; Wiharyanti Nur Lailiyah (Politeknik Negeri Ketapang, 2023)
The production of edamame soybeans in Indonesia has not been able to meet the needs of quite a lot of consumers each year. The use of organic materials such as planting media and fertilization aims to increase the production of edamame soybean plants. This study aims to determine the growth and yield of edamame soybean plants due to the application of various growing media and the dosage of inorganic fertilizers used. This study used a two-factor randomized block design, the first factor was various media (M) and the second factor was fertilizer dose (P). M0 = Soil M1 = Mixture of husk charcoal and soil (1:1) M2 = Mixture of sawdust and soil (1:1) P1 = 25% Recommended dose, P2 = 50% recommended dose, P3 = 75% recommended dose, P4 = 100% recommended dose. These factors were combined into 12 treatments, each treatment was repeated 3 times to produce 36 experimental units. Data analysis used a significant level of variance of 5% and then tested further with the smallest significant difference at the 5% significant level and correlation test. The results showed that there were significant differences in the interaction of various media and fertilizer doses on plant height 6 weeks after planting, plant pod weight and pod weight per hectare.